2003
DOI: 10.1038/sj.npp.1300321
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Activity of the MGLU2/3 Receptor Agonist LY354740 on the Elevated Plus Maze is Associated with the Suppression of Stress-Induced c-Fos in the Hippocampus and Increases in c-Fos Induction in Several Other Stress-Sensitive Brain Regions

Abstract: LY354740 is a potent and selective agonist for group II metabotropic glutamate (mGlu) receptors, mGlu2 and mGlu3 receptors, with anxiolytic activity in several animal models of anxiety, including the elevated plus maze (EPM) test. Here, we studied neuronal activation in mouse brain after EPM exposure in saline-and LY354740-treated mice using c-Fos immunoreactivity as a marker. The effect of LY354740 on c-Fos expression was also studied in cage control (no EPM) mice. Pretreatment with LY354740 (20 mg/kg, s.c.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 73 publications
9
56
1
Order By: Relevance
“…These findings are especially exciting in light of recent clinical studies revealing that group II mGluR agonists have anxiolytic effects in humans (Grillon et al, 2003;Schoepp et al, 2003;Swanson et al, 2005). In the present study, the magnitude of the observed increase in time spent and number of entries into the open arm of the elevated plus maze after pretreatment with BINA were similar to effects observed previously with group II mGluR agonists (Helton et al, 1998;Linden et al, 2004). BINA also prevented the development of stress-induced hyperthermia as observed using both group II mGluR agonists and N-[4Ј-cyanobiphenyl-3-yl)-N-(3-pyridinylmethyl)ethanesulfonamide hydrochloride, a structural analog of LY487379 Rorick-Kehn et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are especially exciting in light of recent clinical studies revealing that group II mGluR agonists have anxiolytic effects in humans (Grillon et al, 2003;Schoepp et al, 2003;Swanson et al, 2005). In the present study, the magnitude of the observed increase in time spent and number of entries into the open arm of the elevated plus maze after pretreatment with BINA were similar to effects observed previously with group II mGluR agonists (Helton et al, 1998;Linden et al, 2004). BINA also prevented the development of stress-induced hyperthermia as observed using both group II mGluR agonists and N-[4Ј-cyanobiphenyl-3-yl)-N-(3-pyridinylmethyl)ethanesulfonamide hydrochloride, a structural analog of LY487379 Rorick-Kehn et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we have observed a more specific activation pattern involving the lateral and medial subdivisions of the CeA, but not the capsular part. Although there are unfortunately only a limited number of studies that have divided the CeA into subregions, it seems that anxiolytic drugs activate neurons primarily in the lateral CeA (Beck and Fibiger 1995;Cohen et al 2003;Linden et al 2004), which are presumably GABAergic (Hitzemann and Hitzemann 1999). At odds with our study, Linden and colleagues found that LY341495 induced neuronal activation also in thalamic areas such as the paraventricular nucleus and the mediodorsal nucleus, hypothalamic nuclei such as the dorsomedial nucleus, midbrain and hindbrain areas such as the substantia nigra or the locus coeruleus.…”
Section: Ly341495-induced C-fos Expression In Wt Micecontrasting
confidence: 84%
“…Activation of mGlu2 and mGlu3 by LY354740 elicits inhibitory responses and has frequently been reported to have anxiolytic-like properties in various anxiety-related tests, such as stressinduced hyperthermia and the elevated plus maze in wildtype (WT) mice (Helton et al 1998;Linden et al 2004;Linden et al 2005a;Monn et al 1997;Spooren et al 2002;Johnson et al 2005;Galici et al 2006). Interestingly, recent studies involving mice lacking mGlu2 or mGlu3 receptors revealed that stimulation of both of these subtypes is necessary to observe anxiolytic-like efficacy of LY354740, since this effect was abolished in both knockout strains (Linden et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…These areas have been implicated in modulation of anxiety/fear in animals and humans (Pratt, 1992) and the acquisition and expression of fear/anxiety responses (Davis et al, 1994). In the amygdala, cFOS studies also suggest that LY354740 prevents disinhibition of circuits that drive fear responses by modulating GABAergic transmission (Linden et al, 2004). Modulation of glutamate-or GABA-mediated excitability in limbic circuits by LY354740 likely represents the key mechanism(s) of action that lead to the anxiolytic effects observed with these agents in preclinical anxiety models as well as human studies (Schoepp et al, 2003).…”
Section: Ly354740 Plasma Concentrationsmentioning
confidence: 99%